Existential Anxiety and Spiritual Coping in the Contemporary Digital Landscape: A Dialogue with Buya Hamka's Sufism - Aswar Aswar; Muhammad Aska Irfani; Alam Khaerul Hidayat; Musdalipa Musdalipa; Mahsur Mahsur (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Existential anxiety has emerged as a growing concern in contemporary digital society, yet its spiritual dimension remains insufficiently explored. This study examines manifestations of existential anxiety and spiritual coping through the philosophical framework of Buya Hamka's Tasawuf Modern. Using a qualitative interpretive approach, it integrates digital content analysis of publicly accessible narratives from TikTok, X, Instagram, and Threads with philosophical textual analysis of Tasawuf Modern. The findings reveal three major manifestations of existential anxiety: loss of meaning in life, digital isolation, and uncertainty about the future, alongside four forms of spiritual coping: gratitude (shukr), contentment (qanā’ah), trust in God (tawakkal), and remembrance of God (dhikr). These findings highlight the relevance of Hamka's modern Sufism (Tasawuf Modern) as a philosophical framework for understanding spiritually grounded coping with existential anxiety in the digital era. Contribution: This article contributes to the growing scholarship on existential anxiety by integrating empirical digital narratives with Buya Hamka's Tasawuf Modern. Rather than treating Hamka's thought as an empirically tested intervention, the study positions Tasawuf Modern as an interpretive philosophical framework for understanding contemporary forms of spiritual coping in digital society.